Association between maternal depression and anxiety episodes and rates of childhood injuries: a cohort study from England - Baker, Ruth; Kendrick, Denise; Tata, Laila J.; Orton, Elizabeth (BMJ Publishing Group Ltd, 2017)
Background: Maternal depression is common and associated with several child health outcomes. The impact on childhood injuries is underexplored, with existing studies relying on maternal reporting of injury occurrences. Using population healthcare databases from England, we assessed the association between maternal depression and/or anxiety episodes and rates of child poisonings, fractures, burns and serious injuries.